The Catalyst of Social Change: Women in Historical Market Dynamics (Kaladarpan कलादर्पण, 2023)
The market is the most imperative dynamic in the world history. Market dynamics play a major and vital role in both the growth and collapse of society. Every society survives with the characteristic of its market. Society is classified according to the characteristics of the market. The importance of the market in studying the rise, growth, crisis, and transformation of society has not been given adequate space in academia. However, it is difficult to understand the historical reason for the growth of society, transformation process, and change by neglecting the market dynamics, which is one of the crucial factors for the transformation of society. Thus, this article tries to illustrate the role of the market in the growth and transformation of society.